An ordinance of His Excellency Edward Viscount Cornbury captain general and governour in chief in and over the provinces of New-York, New-Jersey ... : Whereas the High Court of Chancery held within the province of New-York, by an ordinance of His said Excellency in Council, bearing date the 13th day of June, anno Domini 1702 . ([Printed by William Bradford], 1704)
Establishing fees for the officers of the Court of Chancery.